2020
DOI: 10.3390/app10238696
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Assessing the Quantitative Effects of Heterogeneous Affinity in Malaria Transmission along with Ivermectin Mass Administration

Abstract: Using an agent-based model of malaria, we present numerical evidence that in communities of individuals having an affinity varying within a broad range of values, disease transmission may increase up to 300%. Moreover, our findings provide new insight into how to combine different strategies for the prevention of malaria transmission. In particular, we uncover a relationship between the level of heterogeneity and the level of conventional and unconventional anti-malarial drug administration (ivermectin and gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In addition, our study showed how gender, socioeconomic aspects, and cultural attitudes and beliefs could also play a role in the spread of malaria. Given this multifactorial scenario, several mathematical models have been proposed to tackle specific problems related to malaria transmission in a human community, and a promising impact on disease prevention strategy is provided by “agent-based models” [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study showed how gender, socioeconomic aspects, and cultural attitudes and beliefs could also play a role in the spread of malaria. Given this multifactorial scenario, several mathematical models have been proposed to tackle specific problems related to malaria transmission in a human community, and a promising impact on disease prevention strategy is provided by “agent-based models” [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…To combine results from empirical data with simulations from the agent model introduced and developed in previous works [3,4], we conduct a series of simulations at different levels of disease transmission efficiency. Human-to-mosquito (H-to-M) transmission was defined in terms of the fraction of human disease days with the presence of gametocytemia in blood circulation, henceforth represented as w h .…”
Section: Agent Model For Malarial Spreadingmentioning
confidence: 99%
“…[3]. That model was also used as support for an additional study concerning the presence of heterogeneity in malaria transmission along with the use of ivermectin [4].…”
Section: Agent Model For Malarial Spreadingmentioning
confidence: 99%
See 1 more Smart Citation